IDO Inhibition Facilitates Antitumor Immunity of Vγ9Vδ2 T Cells in Triple-Negative Breast Cancer - Li, Peng; Wu, Ruan; Li, Ke; Yuan, Wenhui; Zeng, Chuqian; Zhang, Yuting; Wang, Xiao; Zhu, Xinhai; Zhou, Jianjun; Li, Ping; Gao, Yunfei (Frontiers in Oncology, 2021)
Triple-negative breast cancer (TNBC) escape from immune-mediated destruction has been associated with immunosuppressive responses that dampen T cell activation. TNBC has a higher expression level of programmed cell death 1-ligand 1 (PD-L1) and indoleamine 2,3-dioxygenase (IDO) compared with other breast cancer subtypes. Nevertheless, clinical studies have revealed that the response rate of immune checkpoint receptor inhibitors (ICIs) for TNBC was relatively low. However, the antitumor responses of human Vγ9Vδ2 T cells or IDO inhibitor in TNBC are unknown. In this study, the data of single-cell RNA-sequencing showed that IDO1 and PD-L1 are co-expressed in TNBC patients. Analysis of the clinical samples demonstrated that Vγ9Vδ2 T cells became exhausted in triple-negative breast cancer patients. Vγ9Vδ2 T cells combined with αPD-L1 cannot further enhance their antitumor responses in vitro and in vivo. We revealed that Vγ9Vδ2 T cells combined with IDO1 inhibitor 1-Methyl-L-tryptophan (1-MT) or Lindrostat had substantial strong therapeutic effects for TNBC. Finally, we found that IDO1 inhibitor promoted T cell’s cytotoxicity by enhancing perforin production. These results converged to strongly support the potential application of Vγ9Vδ2 T cells treated with IDO1 inhibitor for TNBC therapy.